Developing decision-making skills for business - Simon, Julian Lincoln, 1932-1998 (M.E. Sharpe, 2001)
This volume teaches readers how to improve their professional decision-making skills and enhance their ability to develop long-lasting interpersonal relationships with co-workers or clients. It covers a range of topics, including identifying taste and preferences, HRM, and risk and uncertainty.